ASPEK DAN FUNGSI HUKUM LINGKUNGAN DALAM PEMBANGUNAN BERKELANJUTAN - Noor Tri Hastuti (Perspektif, 2003)
The application of Environment Regulation in a sustainable development is to organize and to coordinate many kinds of interests in various aspects. In a sustainable development there are many law aspects such as administrative law, civil law and civil law aspects.